THE IMPORTANCE OF THE “DEBATE” METHOD IN ENGLISH LANGUAGE LESSONS - Komilova Muxtasar Abdunabi qizi (PEDAGOGS, 2025)
Interactive methods play a crucial role in developing students’ communicative competence in foreign language teaching. One such method is debate. This article analyzes the significance of using the debate method in English language lessons, drawing on scientific-theoretical sources and the experience of developed countries. The research findings show that debates significantly enhance students’ oral communication skills, critical thinking abilities, and readiness for interaction, while also boosting learning motivation and self-confidence. The article further explores the methodology and conditions for effectively organizing debates in the classroom and discusses, based on scholarly literature, the role of this method in shaping linguistic competences.